Psychosocial, Behavioral, and Spiritual Determinants of Quality of Life in Chronic Kidney Disease: A Path Analysis Study - Fauzi, Achmad; Ahmedy, Fatimah; Payus, Alvin Oliver; Daud, Maryama Bte Ag.; Reniyah, Reniyah (Universitas Pendidikan Indonesia, 2026)
Introduction: Chronic Kidney Disease (CKD) is a progressive, irreversible condition that impairs physical, psychological, and social functioning, reducing patients’ quality of life (QoL). While factors like treatment adherence, social support, coping, and spirituality have been linked to QoL, few studies have explored their interrelationships in low- and middle-income countries. Objective: This study examined the direct and indirect associations among psychosocial, behavioral, and spiritual factors and quality of life among patients with chronic kidney disease undergoing maintenance hemodialysis in Indonesia using a hypothesized path model. Methods: A cross-sectional study was conducted with 300 adult CKD patients from three hemodialysis centers in Jakarta, selected via consecutive sampling. QoL (KDQOL-36™), social support, treatment adherence, self-efficacy, health literacy, coping strategies, and spiritual well-being were assessed using validated instruments. Path analysis was performed using AMOS version 24, with model fit evaluated using CFI, TLI, RMSEA, and SRMR. Significance was set at p .05. Results: The model showed good fit (CFI = 0.945, TLI = 0.927, RMSEA = 0.057, SRMR = 0.048). Treatment adherence had the strongest direct effect on QoL (β = 0.31, p .001), followed by coping strategies (β = 0.24) and spiritual well-being (β = 0.22). Social support, self-efficacy, and health literacy indirectly influenced QoL through treatment adherence. The highest total effect on QoL was from treatment adherence (β = 0.31), followed by coping (β = 0.24), spirituality (β = 0.22), and social support (β = 0.18). Conclusion: QoL in CKD patients is influenced by treatment adherence, coping, spirituality, and psychosocial support. Holistic, culturally sensitive interventions integrating education, psychological support, and spiritual care are essential to improve outcomes in resource-limited settings.